Crime Data Mining an Indian Perspective - Narwal, N (International Journal of Computer Sciences and Engineering, 2025)
Today Information Technology is used in every domain of life. The traditional age-old system of intelligence and criminal record maintenance are no longer used in the current crime scenario. With the availability of spatial data related to crime can be used to integrate it with latest GPS system to highlight the location of crime and such indication can be used by people to be cautious and alert. This latest technology can be used as an aid to warn and guide people about such happening in the crime prone areas. Manual processes neither provide accurate, reliable and comprehensive data round the clock nor does it help in trend prediction and decision support. It also results in lower productivity and ineffective utilization of manpower. The solution to this ever-increasing problem lies in the effective use of Information Technology. This paper suggests methodology that combines the Geographical Information System with crime data to provide crime data mining.